The possible extension of vicarious liability to cover relations between holding companies and their subsidiaries: Is it plausible and desirable under South African Law? - Mafulela, Tulani Musawenkosi (My University, 2018)
Modern companies in South Africa and elsewhere have embraced the use of corporate group structures. One of the problems arising from such structures is who should bear responsibility towards delictual creditors for unsatisfied judgment debts against insolvent subsidiaries. In such situations, the claims of delictual creditors have often gone uncompensated. Recent events involving large delictual claims worldwide in hazardous industries such as in mining have shown notable barriers to justice, particularly with regards to subsidiary companies’ liability for the harm they cause to third parties. This has been particularly concerning, especially when these large delictual violations have human rights implications. One of the reasons these violations continue to lack adequate recourse is the uneven distribution of risks and liabilities between holding companies and their subsidiaries. This research is primarily concerned with whether a holding company of an insolvent subsidiary should bear some responsibility towards the latter’s uncompensated delict creditors. Traditional considerations of holding company liability of this nature have been mainly located within corporate law. Remedies such as the veil piecing and director’s liability have been the primary mechanisms through which holding company liability has been implemented. This research seeks to explore further possibilities by questioning whether the rules of vicarious liability in South Africa ought to be developed to create liability between a parent company and its subsidiary.
Masters of laws specializing in business and commercial law,2018